The toxic effects of pyrethroid deltamethrin on the common carp (Cyprinus carpio L.) embryos and larvae - Köprücü, K; Aydin, R (Academic Press Inc Elsevier Science, 2004)
Deltamethrin, a synthetic pyrethroid pesticide contaminating aquatic ecosystems as a pollutant, was investigated in the present study for toxic effects on embryos and larvae of common carp, Cyprinus carpio as a model. The control and five test experiments were repeated five times. The water temperature in the experimental units was kept at 24 +/- 1 degreesC. The number of dead embryos significantly increased in response to deltamethrin concentrations 0.005, 0.05, 0.5, 5, 25, and 50 mug L-1 (p < 0.05 for each cases) Dose-response decreases in hatching success were recorded as 75.2, 64.6, 47.4, 26.0, 14.4, and 9.0%, respectively. The lowest concentration of deltamethrin (0.005 mug L-1) produced a significantly decrease in number of dead larvae compared to control group (p < 0.05). With increasing deltamethrin concentrations, the larvae exposed duration 1-48 h significantly increased: the number of dead larvae (p < 0.05 for each cases). The 48 h LC50 values (with 95% confidence limits) of deltamethrin for common carp embryos and larvae were estimated as 0.213 (0.103-0.404) and 0.074 (0.011-0.260) mug L-1, respectively. The results provide evidence that deltamethrin pollution may have an adverse effect on the reproduction and development of carp, which should be considered when this chemical is used in agricultural areas near aquatic ecosystems. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: common carp; Cyprinus carpio; embryo; larvae; pyrethroid pesticide; deltamethrin